Fritsa Staala badania nad rytuałem, mantrą i religią = Frits Staal`s research on the ritual, mantra and religion . - Czyżykowski, Robert (Przegla̜d religioznawczy, 2017)
A paper is devoted to the research of the late Frits Staal concerning the ritual and religion. Staal`s scientific achievements were especially significant in Ritual Studies and the phenomena of mysticism. As indicates interest in his work he is one of the most prominent figure in Ritual Studies. Staal is also considered the initiator of the modern field research of Vedic ritual. The paper is the attempt to review the work of Staal and present the use-fulness of his thesis for Religious Studies. According to Staal the study of religion can lead us to the very primordial structures of human thinking and basics of humanity. It can throw the light on evolutional structures which contain the genesis of language and cognitive abilities which were shaping along with the evolution of the religious phenomena.